Association between anti-CMV IgG and salivary levels of IL‐6 and TNF-α in chronic periodontitis - Heba K Mahmood; Batool H Al-Ghurabi (College of Dentistry/ University of Baghdad, 2020)
Background: Periodontitis is an infection attributable to multiple infectious; it causes an interrelated cellular and humoral host immune responses. Recent reports have indicated that human cytomegalovirus (HCMV) may contribute to pathogenesis of periodontitis. The HCMV can stimulate the release of cytokines from inflammatory and non-inflammatory cells and weaken the periodontal immune defense. This study aimed to reveal the presence of anti-CMV IgG, and determine the levels of IL‐6 and TNF-α and to correlate the presence of cytomegalovirus (CMV) with cytokines levels. Materials and Methods: Forty patients with chronic periodontitis and 40 healthy control subjects (their age and sex were matched with the patients) were involved in this study. Periodontal parameters used in this study included plaque index (PLI), gingival index (GI), probing pocket depth (PPD), clinical attachment level (CAL) and bleeding on probing (BOP). Saliva samples were taken from all subjects. ELISA was carried out to estimate the levels of anti-CMV IgG, IL‐6 and TNF-α. Statistical tests used involved t-test, Mann-Whitney, Chi-square, Fisher exact and spearman's correlation test. Results: This study found a significant difference (p<0.05) in the frequency of anti-CMV IgG in saliva between patients and controls. The number and percentage of patients group who had positive for anti-CMV IgG were 14 (35%), while controls were 5 (12.5%). A significant increase was found in mean of PPD, CAL and BOP among patients with the positive IgG as compared to those patients with the negative IgG. In addition, there was a significant elevation in the salivary levels of IL‐6 and TNF-α in patients compared with healthy controls. IL- 6 was significantly associated with GI and BOP, whereas TNF-α was significantly associated with PPD and CAL. On the other hand, there was a significant correlation between TNF-α and anti- CMV IgG. Conclusion: The findings revealed that the significant association between the presence of virus with periodontal parameters and cytokines level in patients group gives additional evidence toward the potential importance of the direct and indirect effects of CMV infection in periodontitis. Keywords: Periodontitis, Anti- CMV IgG, Cytokines.